2020
DOI: 10.1016/j.clinbiomech.2020.105090
|View full text |Cite
|
Sign up to set email alerts
|

Lunate loads following different osteotomies used to treat Kienböck's disease: A 3D finite element analysis

Abstract: Background: One of most accepted principles for treating Kienböck's disease before wrist degeneration settles in is to decompress the lunate by an osteotomy. Several osteotomies have been proposed since 1935. However, they are based on biomechanical hypotheses that are sometimes conflicting: This study compares the decompression effect of radius transverse shortening, radius lateral closing and medial closing wedge osteotomies, capitate shorteningwith and without hamate shorteningand a Camembert-type radius we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…JLPs initially had the goal of achieving neutral ulnar balance in cases of negative ulnar variance, to counteract the predisposing effect for developing KD described by Hulten in the late 1920 s (Hulten, 1929). Although there is much doubt about this concept, these techniques do mechanically decompress the lunate in different degrees (Camus et al., 2020) and usually provide good functional results compared with the unpredictable long-term natural course of KD (Viljakka et al., 2014). Other procedures focused on treating the biological aspect of KD, such as VBGs, can be combined with a JLP in a multimodal approach and salvage procedures can still be performed if needed.…”
Section: Treatment Of Kdmentioning
confidence: 99%
See 2 more Smart Citations
“…JLPs initially had the goal of achieving neutral ulnar balance in cases of negative ulnar variance, to counteract the predisposing effect for developing KD described by Hulten in the late 1920 s (Hulten, 1929). Although there is much doubt about this concept, these techniques do mechanically decompress the lunate in different degrees (Camus et al., 2020) and usually provide good functional results compared with the unpredictable long-term natural course of KD (Viljakka et al., 2014). Other procedures focused on treating the biological aspect of KD, such as VBGs, can be combined with a JLP in a multimodal approach and salvage procedures can still be performed if needed.…”
Section: Treatment Of Kdmentioning
confidence: 99%
“…The selective shortening wedge osteotomy or ‘camembert’ osteotomy shortens only the part of the radius facing the lunate, offloading the bone without decompressing the scaphoid as is done in the other osteotomies. It may need an associated ulnar wedge osteotomy, but it has the most beneficial biomechanical effect (Camus et al., 2020).…”
Section: Treatment Of Kdmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical outcomes have been generally satisfactory across the spectrum of osteotomy techniques; however, there is conflicting evidence. 3 , 4 , 5 , 6 A recent systematic review showed superior clinical outcomes including pain and wrist range of motion in cases of Kienböck’s disease treated with radial osteotomy compared with cases treated nonsurgically. 4 Importantly, the authors noted that the radial osteotomy group had more advanced disease than the nonsurgical group.…”
mentioning
confidence: 99%
“…A biomechanical study has validated the decompressive effect of radial osteotomy on the lunate. 5 The magnitude of lunate unloading substantially varied between osteotomy techniques, with some techniques providing minimal decrease in radiolunate loading.…”
mentioning
confidence: 99%